2019
DOI: 10.4162/nrp.2019.13.3.222
|View full text |Cite
|
Sign up to set email alerts
|

Impact of socio-demographic factors, lifestyle and health status on nutritional status among the elderly in Taiwan

Abstract: BACKGROUND/OBJECTIVES Aging is an imperative problem for many countries in this century, and presents several challenges for the maintenance of good nutritional status. This study aims to assess the impact of socio-demographic factors, lifestyle and health status on the nutritional status among the elderly in Taiwan. SUBJECTS/METHODS A cross-sectional study was carried out in Taiwan. Data were obtained from the Mei Jau Health Management Institution, which is a private h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 51 publications
3
23
2
3
Order By: Relevance
“…Multinomial logistic regression (MLR) analysis by using R statistical software was applied to estimate the influence of health checkup test results, including blood pressure, pulse rate, and blood uric acid, on health status. MLR does not assume a linear relationship between the dependent and independent variables [ 34 ], and there are studies that have generated dependent variables from independent variables [ 35 ]. For the “healthy” category, the number of cases is only two (0.7%) which is not representative of the total sample size of 271.…”
Section: Resultsmentioning
confidence: 99%
“…Multinomial logistic regression (MLR) analysis by using R statistical software was applied to estimate the influence of health checkup test results, including blood pressure, pulse rate, and blood uric acid, on health status. MLR does not assume a linear relationship between the dependent and independent variables [ 34 ], and there are studies that have generated dependent variables from independent variables [ 35 ]. For the “healthy” category, the number of cases is only two (0.7%) which is not representative of the total sample size of 271.…”
Section: Resultsmentioning
confidence: 99%
“…The trend of increasing morbidity and mortality in the elderly caused by the constant consumption of alcohol has become more obvious in recent years [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are different alcohol use patterns among European countries and the prevalence of alcohol use disorders, alcohol consumption patterns in the elderly are linked not only to certain cultural patterns of behaviour and aging-related health conditions, but also to the need for relaxation [11][12][13]. On the relevant medical databases, at this moment, few studies are available on alcohol consumption among older people, but the data are very different and there is no systematic data analysis on this topic [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A cornerstone for healthy aging is optimal nutritional status. Early identification of older adults who are at risk for insufficient caloric intake and nutrient adequacy, termed nutritional risk, is paramount to maintaining health, independence, quality of life, and longevity [ 9 , 10 ]. Most studies have reported sex-specific differences in the nutritional status and community integration of elderly individuals.…”
Section: Introductionmentioning
confidence: 99%